Prophylaxis of infection after appendicectomy: a survey of current surgical practice. Issue 6255 (13th December 1980) - Campbell, W B
Abstract : Two hundred and eighty questionnaires were sent to junior surgical staff throughout England inquiring about their use of systemic antibiotic prophylaxis, topical antibacterial agents, and surgical drainage in appendicectomy. One hundred and seventy-five (63%) replies were received from 81 of the 87 hospitals included in the survey. Prophylactic systemic antibiotics were used by 78 surgeons (46%) when operating on a normal appendix but by 168 (99%) when the organ had perforated. Most surgeons started antibiotics before operation, but proportionately fewer did so when the appendix was gangrenous or perforated. Patients with severe contamination tended to receive longer courses of antibiotics, although the duration of administration varied considerably. Metronidazole was included in over 95% of all the prophylactic regimens and was often combined with other drugs when the appendix was gangrenous and perforated. Topical antibacterial agents were applied to the wound routinely by only 45 surgeons (26%), although 106 (61%) used them sometimes. Povidone-iodine was the agent most commonly used. Only 98 surgeons (56%) ever drained appendicectomy wounds, while 135 (77%) sometimes drained the peritoneal cavity. Evidence suggests that present methods of giving systemic antibiotic prophylaxis should continue, but that topical agents and surgical drainage are perhaps unnecessary when surgeons are confident of the efficacy of the systemic treatment used.